Eksistensi Perpustakaan UIN Sunan Kalijaga Yogyakarta dalam pelayanan pencarian informasi di era Google - Muhamad Syahrul Mubarok; Silvaenlevi - (FPPTI Jawa Tengah, 2024)
The library in the past was once a curator of historical collections, and was the place where a lever of knowledge began. However, at this time Google appeared, one of the best-selling, and popular search engine products whose level of use in cyberspace is very high for a variety of information search activities ranging from education, research, and recreation. Google equals that it can even surpass the usefulness of libraries that were places where information in the era before google was stored, so from there it is necessary to know about how libraries, especially colleges in maintaining their existence. The method used in this study is descriptive qualitative, an approach to explore and understand the meaning of a number of individuals or groups of people who are considered to be derived from social or humanitarian problems and is also supported by literature studies carried out by analyzing data through activities to collect various sources relevant to the topic under study, such as books, scientific journals, proceedings, nor other scientific articles. The result of this research is that the UIN Sunan Kalijaga library has a user education program aimed at users to be able to find out where and how to get information correctly both in the library, and on Google. In addition, the library also adopts products and features owned by Google such as Google Assistant and search customization features. The library is also active in direct communication both verbally, and also with the media, such as instagram.